Implementation of the Principles of Free, Prior and Informed Consent in the Field of Natural Resources Utilization within the Indonesian Regulatory Framework: Implementasi Prinsip Free, Prior and Informed Consent Pada Bidang Pemanfaatan Sumber Daya Alam dalam Kerangka Regulasi Indonesia - Winarsih, Winarsih; Wulandari, Cahya (Annual Review of Legal Studies, 2024)
Free, prior and informed consent (FPIC) is one of the principles that emerged from international declarations and conventions. Indonesia is a country that is active in several conventions and declarations. However, there is no recognition in national regulations that explicitly incorporates FPIC elements in their entirety. On the other hand, there is a prolonged conflict between indigenous communities and project initiators resulting from various kinds of problems. This article aims to conduct an analysis related to FPIC in regulations in Indonesia both at the national and regional levels. This research uses normative juridical methods using library materials as the main source. The results of this research are: First, FPIC has basically begun to be recognized in regulations at the central level. However, this recognition is still partial and implicit. Second, in regulations at the regional level such as Minahasa Regency, Bengkayang Regency and Central Sulawesi Province, several elements of FPIC have also begun to be absorbed and explicitly recognized. This is marked by the preparation of general guidelines for implementing FPIC in the form of a Regulation of the Governor of Central Sulawesi Province.